Conclusion on the peer review of the pesticide human health risk assessment of the active substance chlorpyrifos. (22nd April 2014) - ,
Abstract: The European Food Safety Authority (EFSA) was asked by the European Commission to perform a human health risk assessment of chlorpyrifos. In this context the conclusions of EFSA concerning the toxicological risk assessment and the human health risk assessment for the active substance chlorpyrifos are reported. The context of the evaluation was that required by the European Commission in accordance with Article 21 of Regulation (EC) No 1107/2009 to review the approval of active substances in light of new scientific and technical knowledge and monitoring data. The conclusions were reached on the basis of the evaluation of the authorised representative uses of chlorpyrifos as an insecticide on table and wine grapes. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified for re‐entry workers for all representative uses. The use of chlorpyrifos on table grapes according to the GAP defined as a single application at 648 g a.s./ha leads to a significant exceedance of the acute reference dose (ARfD).